Enteric, hepatic and muscle tissue development of goat kids fed with lyophilized bovine colostrum. Issue 2 (25th February 2013) - Moretti, D. B.; Nordi, W. M.; Lima, A. L.; Pauletti, P.; Machado‐Neto, R.
Summary The objective of this study was to investigate the development of the enteric, hepatic and muscle tissues in goat kids fed with lyophilized bovine colostrum in the transition period of passive immunity to early active immunity. At 0, 7 and 14 h of life, 15 male newborns received 5% of their body weight of lyophilized bovine colostrum and 14 male newborns received goat colostrum, both with 55 mg/ml of IgG. Samples of the duodenum, jejunum, ileum, liver and muscle were collected at 18, 36 and 96 h of life to quantify total protein, DNA and RNA contents. In the jejunum and ileum, the highest levels of total protein and higher protein/RNA ratio were observed at 18 h (p < 0.05). There were no differences in DNA contents in any intestinal segment (p > 0.05). At 96 h, maximum levels of RNA were observed in the jejunum and ileum (p < 0.05) and higher RNA/DNA ratio in the three intestinal segments (p < 0.05), showing increased ability to synthesize intracellular RNA and proteins. The LBC group showed higher protein content and higher protein/DNA and protein/RNA ratios in the jejunum, a higher DNA content in the liver (p < 0.05) and a higher protein/RNA ratio in the muscle tissue (p < 0.05). In the muscle, higher protein and DNA levels were also found at 96 h (p < 0.05). Indicators of cellular activity suggest greater absorption of proteins from lyophilized bovine colostrum and increased cell maturity in the enteric and muscle tissues in the first hours of goat kids' life.